Professional-Moral Ethics and Image of a Modern Pedagogue (Eurasian Journal of Learning and Academic Teaching, 2022)
The conditions of globalization of all socio-economic phenomena in the world, information and technological innovations and market relations based on the competitiveness of workers, steadily require significant changes in the system of school, secondary special and university education. In the system of such renewal of university education, the main place belongs to the search for optimal ways of professional development of the teaching staff. Of great theoretical and practical importance in this regard is the search for psychological and pedagogical patterns for the development of professional competence of future specialists. Currently, all the leading universities in the world train specialists based on the leading category of life – competence